2020
DOI: 10.1017/s0142716420000430
|View full text |Cite
|
Sign up to set email alerts
|

The structure of developing semantic networks: Evidence from single and multiple nominal word associations in young monolingual and bilingual readers

Abstract: The present study focuses on the effect of an important methodological choice in word association studies in children: the elicitation of single versus multiple responses. This choice has been shown to affect the numbers and types of associations adults produce, however, little is known about how it affects children’s word associations. A total of 11,725 associations to 80 nouns from 207 monolingual and bilingual minority children were classified according to a detailed coding system, and differences between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(95 reference statements)
0
9
0
1
Order By: Relevance
“…Further, most studies investigating the organization of L2 mental lexicon either addressed meaning-based and form-based associations or paradigmatic and syntagmatic associations, only a few studies have dug deep into the subcategories of paradigmatic and syntagmatic associations ( Fitzpatrick, 2007 ; Zhang, 2010a , b ; Cremer et al, 2011 ; Khazaeenezhad and Alibabaee, 2013 ; Feng, 2014 ; Li and Wang, 2016b ; El-Dakhs, 2017 ; Spätgens and Schoonen, 2020 ). In the few existing studies, paradigmatic and syntagmatic associations of L2 mental lexicon have been divided into different subcategories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, most studies investigating the organization of L2 mental lexicon either addressed meaning-based and form-based associations or paradigmatic and syntagmatic associations, only a few studies have dug deep into the subcategories of paradigmatic and syntagmatic associations ( Fitzpatrick, 2007 ; Zhang, 2010a , b ; Cremer et al, 2011 ; Khazaeenezhad and Alibabaee, 2013 ; Feng, 2014 ; Li and Wang, 2016b ; El-Dakhs, 2017 ; Spätgens and Schoonen, 2020 ). In the few existing studies, paradigmatic and syntagmatic associations of L2 mental lexicon have been divided into different subcategories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous work has demonstrated the significant influence of age on WAT performance (e.g., Cremer et al, 2011;Spätgens & Schoonen, 2020;Nelson, 1977). Entwisle (1966) showed that older monolingual children (e.g., fifth grade) produced more responses commonly shared among group members than younger monolingual children (e.g., preschoolers), suggesting greater within-group homogeneity that characterizes the community.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of bilingualism on semantic convergence in children's WAT performance has received much less attention when compared to other semantic domains, such as picture identification and naming abilities that indicate vocabulary breadth. Notably, existing work on WAT in bilingual children has focused on analyzing qualitative aspects of responses, such as meaning-related versus form-based (Cremer et al, 2011), paradigmatic versus syntagmatic (Holmström et al, 2016;Namei, 2004;Sheng et al, 2006), or context-independent versus context-dependent responses (Spätgens & Schoonen, 2020). Results from these studies are far from conclusive: previous work has found subtle advantages in producing the more advanced paradigmatic associates in bilingual children (Holmström et al, 2016;Sheng et al, 2006), subtle disadvantages in bilingual children (Namei, 2004) though the effect of language backgrounds was more limited compared to the effect of age (e.g., Cremer et al, 2011), or comparable associative preferences between monolingual and bilingual children (Spätgens & Schoonen, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations